Genetic background influences tumour development in heterozygous Men1 knockout mice. Issue 5 (May 2020) - Lines, Kate E; Javid, Mahsa; Reed, Anita A C; Walls, Gerard V; Stevenson, Mark; Simon, Michelle; Kooblall, Kreepa G; Piret, Sian E; Christie, Paul T; Newey, Paul J; Mallon, Ann-Marie; Thakker, Rajesh V
Abstract : Multiple endocrine neoplasia type 1 (MEN1), an autosomal dominant disorder caused by MEN1 germline mutations, is characterised by parathyroid, pancreatic and pituitary tumours. MEN1 mutations also cause familial isolated primary hyperparathyroidism (FIHP), a milder condition causing hyperparathyroidism only. Identical mutations can cause either MEN1 or FIHP in different families, thereby implicating a role for genetic modifiers in altering phenotypic expression of tumours. We therefore investigated the effects of genetic background and potential for genetic modifiers on tumour development in adult Men1 +/- mice, which develop tumours of the parathyroids, pancreatic islets, anterior pituitary, adrenal cortex and gonads, that had been backcrossed to generate C57BL/6 and 129S6/SvEv congenic strains. A total of 275 Men1 +/- mice, aged 5–26 months were macroscopically studied, and this revealed that genetic background significantly influenced the development of pituitary, adrenal and ovarian tumours, which occurred in mice over 12 months of age and more frequently in C57BL/6 females, 129S6/SvEv males and 129S6/SvEv females, respectively. Moreover, pituitary and adrenal tumours developed earlier, in C57BL/6 males and 129S6/SvEv females, respectively, and pancreatic and testicular tumours developed earlier in 129S6/SvEv males. Furthermore, glucagon-positive staining pancreatic tumours occurred more frequently in 129S6/SvEv Men1 +/- mice. Whole genome sequence analysis of 129S6/SvEv and C57BL/6 Men1 +/- mice revealed >54, 000 different variants in >300 genes. These included, Coq7, Dmpk, Ccne2, Kras, Wnt2b, Il3ra and Tnfrsf10a, and qRT-PCR analysis revealed that Kras was significantly higher in pituitaries of male 129S6/SvEv mice. Thus, our results demonstrate that Kras and other genes could represent possible genetic modifiers of Men1 .